707 Dermal absorption of fluoride and hydrogen ions following topical exposure to hydrofluoric acid - Kilo, Sonja; Dennerlein, Kathrin; Korinth, Gintautas; Göen, Thomas; Drexler, Hans (Occupational and Environmental Medicine 2018, 2018)
Introduction Despite being an extremely hazardous liquid, hydrofluoric acid (HF) is commonly used in industry due to its unique chemical properties. Chemically HF is defined as a ‘weak’ acid but fluoride ions can induce serious systemic toxic effects. Upon contact with low concentrated HF, symptoms such as pain or local lesions may be delayed. The aim of this study was to characterise changes in intradermal pH and dermal fluoride penetration following HF application. Methods A static diffusion cell model was used to study dermal fluoride penetration for 6–72 hour following application of varying amounts of HF (c=5%–50%, 100–160 µl/0.64cm2, 1–10 min.) on human skin (thickness 0.9 or 2.5 mm). Intra- and transdermal amounts of fluoride and intradermal pH were determined. Result Transdermal penetration of fluoride increased exponentially with increasing HF concentration. In addition, penetration increased four-times by extending the exposure time from 1 to 3 min. No further increase was seen with longer HF application (5 and 10 min.). The increased amount of HF penetrated through 0.9 mm compared to 2.5 mm skin within one hour was levelled out at later time points. Intradermal accumulation of fluoride increased dose-dependently but to a lower degree. Intradermal pH dropped with increasing HF concentration and exposure time. Additionally, the lag time between HF application and onset of pH changes decreased with increasing HF concentration and application time. Discussion The results of the present study show that following 3 min. HF application maximal amounts of fluorides seem to have penetrated the skin. The longer lag time in pH drop with lower concentrated HF might explain the delay between HF contact and onset of pai

914 Hydrofluoric acid – effects of skin decontamination on the bioavailability of fluoride - Dennerlein, Kathrin; Hahn, Theresa; Göen, Thomas; Drexler, Hans; Kilo, Sonja (2018)
Introduction After dermal contact to occupational hazardous substances the cleaning of exposed skin areas is an important first aid measure to reduce adverse health effects. Due to possible severe systemic intoxication following dermal exposure to hydrofluoric acid (HF) the decontamination of skin should focus on the inactivation of free fluoride ions. The present ex-vivo study investigated the effects of exposure duration and different antidotes on the potential systemic uptake of fluoride. Methods The transdermal penetration of HF (c=30%) through excised human skin was investigated by using static diffusion cells. After dermal application of the acid (100 µl/0.64 cm2) for 1 min the excess was removed using one dry cotton swab. Subsequently, the skin was cleaned with water, calcium gluconate (CaGl), polyethylene glycol (PEG) 400 or hexafluorine© using a standardised protocol. In a further study, the application time was extended to 3 min to assess the effect of exposure duration. Chemical analyses of fluoride were carried out by GC-MS or via a fluoride-sensitive electrode. Result Extension of the exposure time from 1 to 3 min led to an enhancement in the transdermal penetration of fluoride, however with similar penetration kinetics. At the end of experiments (6 hour) a 7–fold higher fluoride amount was detected in the receptor fluid (16 vs 114 µg). In all test series maximum flux was achieved within the first hour past exposure. Decontamination of the skin reduced the cumulative penetrated amount of fluoride by 28% (PEG 400), 49% (water) and 64% (CaGl/hexafluorine©) compared to control. Discussion The results indicate that the systemic uptake of fluoride ions and therefore possible systemic intoxication after exposure to hydrofluoric acid can be diminished by shortening the exposure duration. Reduction was further increased by decontamination of skin – most by substances which are known to supply the complexation of fluoride ion

Calcium, magnesium and aluminium ions as decontaminating agents against dermal fluoride absorption following hydrofluoric acid exposure - Mini Vijayan, Suvarna; Göen, Thomas; Dennerlein, Kathrin; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2021)
The fluoride ions of the industrially largely irreplaceable, locally corrosive hydrofluoric acid (HF) can scavenge cations in biological tissues, which explains their high toxic potential, and also leads to local acidification through proton release. The influence of three complexing agents, calcium (Ca2+) gluconate (as 2.5% Ca2+gel and individually (2.84%) or commercially (10%) formulated Ca2+solution), magnesium (Mg2+) gluconate (2.84%) solution and aluminium (Al3+) solution (Hexafluorine®, pure and diluted) on the absorption of fluoride following HF exposure (1–3 min, 100 μl, 30%/0.64 cm2) through human skin was investigated in an ex-vivo diffusion cell model. Fluoride absorption was assessed over 6–24 h and analysed with a fluoride electrode. Decreasing the contamination time reduced the fluoride absorption distinctly which was further reduced by the application of fluoride-binding decontamination agents (Ca2+, Mg2+, Al3+) or water alone without being significantly different. Ca2+ appeared slightly more effective than Mg2+ in reducing fluoride absorption. Moreover, the addition of pH adjusting buffer promoted the decontamination efficacy. Fluoride-binding agents can facilitate the decontamination of dermal HF exposure. However, prompt decontamination appeared to be the key to successful limitation of fluoride absorption and pushes the choice of decontamination agent almost into the background.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Aluminium; Calcium gluconate; Decontamination; Fluoride absorption; Human skin; Hydrofluoric acid

Dermal absorption and skin damage following hydrofluoric acid exposure in an ex vivo human skin model - Dennerlein, Kathrin; Kiesewetter, Franklin; Kilo, Sonja; Jäger, Thomas; Göen, Thomas; Korinth, Gintautas; Drexler, Hans (Toxicology Letters, 2016)
The wide industrial use of hydrofluoric acid (HF) poses a high risk for accidental dermal exposure. Despite local and systemic hazards associated with HF, information on percutaneous penetration and tissue damage is rare. In the present ex vivo study, the dermal absorption of HF (detected in terms of fluoride ions) was quantified and the skin damaging potential as a function of concentration and exposure duration was assessed. Percutaneous penetration of HF (c=5, 30, and 50%) at 3 exposure durations (3, 5, and 10min) was investigated in a static diffusion cell model using freshly excised human skin. Alterations of skin were histologically evaluated. HF rapidly penetrated through skin under formation of a considerable intradermal reservoir ( 13-67% of total absorbed fluoride). Histologically, epidermal alterations were detected already after exposure to 5% HF for 3min. The degree of skin damage increased with rising concentration and exposure duration leading to coagulation necrosis. For HF concentrations of >=30%, skin damage progressed into deeper skin layers. Topically applied HF concentration was the principal parameter determining HF induced skin effects. The intradermal HF retention capacity associated with progression and prolongation of HF induced skin effects must be considered in the review of skin decontamination procedures.
EVALuna2:9745

Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja; Drexler, Hans; Kilo, Sonja (Chemosphere, 2017)
Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N-phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 ?g/0.64 cm2. The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's.
EVALuna2:9769

Evaluation of the effect of skin cleaning procedures on the dermal absorption of chemicals - Dennerlein, Kathrin; Jäger, Thomas; Göen, Thomas; Kilo, Sonja; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2015)
To reduce the internal exposure, skin decontamination is the most important measure after dermal contact to chemicals. However, no harmonized skin cleaning procedure for experimental ex vivo studies is published. In our study, the impact of two skin cleaning techniques on dermal penetration kinetics and intradermal deposition of 1,4-dioxane, 5% hydrofluoric acid (HF, detected in terms of fluoride ions), and anisole was evaluated to develop a reliable ex vivo skin cleaning method using the diffusion cell technique. After exposure (duration: 3 min (HF); 1h (1,4-dioxane and anisole)) of excised human skin (n=6-8) decontamination was performed by (I) water-soaked cotton swabs or (II) direct application of water on the exposure area. The effect of skin cleaning was investigated by analysing the concentration time course of chemicals in the receptor fluid of diffusion cells and by determining the deposition in skin. Both skin cleaning procedures reduced the amount of fluoride in the skin compartments (p<0.05) and the receptor fluid (p<0.1). However, the effect of cleaning on the dermal absorption of the organic test compounds was not significant. The results demonstrate the suitability of the applied ex vivo protocol for investigating the effectiveness of skin cleaning measures following dermal exposure. In addition, data reveal that the determination of test compounds in both, skin compartments as well as receptor fluid as equivalent for the systemic uptake needs to be considered in studies assessing the effectiveness of skin decontamination procedures.
EVALuna2:9730

Evaluation on the reliability of the permeability coefficient (Kp) to assess the percutaneous penetration property of chemicals on the basis of Flynn's dataset - Kladt, Carolin; Dennerlein, Kathrin; Göen, Thomas; Drexler, Hans; Korinth, Gintautas (International Archives of Occupational and Environmental Health, 2018)
PURPOSE: The permeability coefficient (Kp) is often used for prediction of the dermal penetration of chemicals. Mathematical models have mostly been derived on Kp data basis. However, confusing Kp values are reported, questioning the general reliability of this parameter. In this study, we tested the plausibility of Kp values expressing the dermal penetration velocity (cm h-1) of chemicals on a larger dataset from literature. METHODS: Kp was applied for the calculation of the time for penetration through skin membranes of defined thickness (tCrossSkin). Kp values were obtained from Flynn's dataset (1990), containing data determined mostly under similar experimental conditions using diffusion cells. Further skin penetration parameters, e.g., times at which the chemicals were firstly measured in the receptor phase, lag times, steady-state times, and exposure duration, where available, were related to Kp values. The data congruence was tested comparing Kp values from Flynn's dataset with those reported in the EDETOX database. Variables, which could bias the results, such as different experimental protocols and research groups were also considered. RESULTS: Kp data for 94 chemicals matched the inclusion criteria were evaluated. According to the Kp values, 21 (22%) compounds would require longer than 100 h, and 20 (21%) further compounds longer than 10 h of exposure to penetrate skin membranes of 0.01-2.5 mm thickness. Obviously, erroneous Kp were found in studies of almost all research groups in Flynn's database, indicating that neither the observer nor the experimental conditions alone biased the values. CONCLUSIONS: Our evaluation demonstrates high implausibility of Kp values to represent the dermal penetration velocity and supports general invalidity of the parameter for implementation in studies using skin membranes. The Kp should not be used to characterize the percutaneous penetration of chemicals or in risk assessment without verification.
EVALuna2:34675

Influence of artificial sebum on the dermal absorption of chemicals in excised human skin: A proof-of-concept study - Schneider, Daniela; Dennerlein, Kathrin; Göen, Thomas; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2016)
In an initial diffusion cell study, the influence of artificial sebum on dermal penetration and intradermal reservoir of ethanol and toluene was investigated in comparison with the effects of a skin cream (o/w- and w/o-emulsion) and untreated (control) skin. Human skin was exposed to neat ethanol and toluene for 4h, respectively. During the experiments, the penetration of the compounds was assessed in the receptor fluid. The amounts of the test compounds in the skin were determined at the end of exposure. In the control experiments, 42% of the total resorbed ethanol amounts were found in the intradermal reservoir after 4h, whereas 82% of the toluene amounts were found in the skin compartments. The treatment with artificial sebum showed no significant differences in dermal absorption of both test compounds compared to control skin. In contrast, the treatment with skin cream increased the percutaneous penetration (p<0.001) and the intradermal reservoir of ethanol 2-fold but not of toluene. In all exposure scenarios, a relevant intradermal reservoir was formed. The results indicate that sebum does not influence the percutaneous penetration and the intradermal reservoir of epidermally applied chemicals, whereas the application of skin creams may increase the dermal penetration of the compounds.
EVALuna2:9746